Ciri Budaya Prasejarah pada Sistem Bercocoktanam Masyarakat Suku Dani di Lembah Baliem - Djami, Erlin Novita Idje (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
Prehistoric featured life is still found in Dani tribe society who inhabit Baliem valley in the mountainous area of central Papua. The tribe’s simple life still maintain their gathered way of life. They live their nomadic cultivating while using sheer technology such as stone, digging stick and spade. In their cultivation activities, The Danis share strict rules between their male and female members. Men obliged to open new land, to build fench and shed, while women binded to do plantation until harvesting which makes women time are spent mostly in the field.The Danis livelihood is so affected by environment and kinship factors in governancing and managing land, social strata in task division between men and women, and also their belief in their anchestor’s spirits which can bring about fortune and prosperity.